Metallicity-dependent nucleosynthetic yields of Type Ia supernovae originating from double detonations of sub-MCh white dwarfs - Gronow, Sabrina; Côté, Benoit; Lach, Florian; Seitenzahl, Ivo R.; Collins, Christine E.; Sim, Stuart A.; Röpke, Friedrich (Astronomy and astrophysics, 2021)
Double detonations in sub-Chandrasekhar mass carbon-oxygen white dwarfs (WD) with helium shells ares potential explosion mechanisms for Type Ia supernovae. The mechanism consists of a shell detonation and subsequent core detonation. The focus of our study is the effect of the progenitor metallicity on the nucleosynthetic yields. For this, we computed and analyzed a set of 11 different models with varying core and shell masses at four different metallicities each. This results in a total of 44 models at metallicities between 0.01 Z⊙ and 3 Z⊙. Our models show a strong impact of the metallicity in the high-density regime. The presence of 22Ne causes a neutron-excess that shifts the production from 56Ni to stable isotopes such as 54Fe and 58Ni in the α-rich freeze-out regime. The isotopes of the metallicity implementation further serve as seed nuclei for additional reactions in the shell detonation. The production of 55Mn increases with metallicity, confirming the results of previous work. A comparison of elemental ratios relative to iron shows a good match to solar values for some models. Super-solar values are reached for Mn at 3 Z⊙ and solar values in some models at Z⊙. This indicates that the required contribution of Type Ia supernovae originating from Chandrasekhar-mass WDs can be lower than estimated in previous work to reach solar values of [Mn/Fe] at [Fe/H] = 0. Our galactic chemical evolution models suggest that Type Ia supernovae from sub-Chandrasekhar mass white dwarfs, along with core-collapse supernovae, could account for more than 80% of the solar Mn abundance. Using metallicity-dependent Type Ia supernova yields helps to reproduce the upward trend of [Mn/Fe] as a function of metallicity for the solar neighborhood. These chemical evolution predictions, however, depend on the massive star yields adopted in the calculations.
Gesehen am 20.01.2022
Im Titel ist der Ausdruck "Ch" tiefgestellt